FENANTROLİN KOMPLEKSLERİNİN DİELEKTRİK ÖZELLİKLERİNİN İNCELENMESİ - AKGÜL, ÜNAL (Fırat Üniveristesi, 2007)
Bu tezde, 1,10-Fenantrolinin komplekslerinin X-ışını difraksiyonu, AC elektriksel iletkenliği ve dielektrik özellikleri incelendi. X-ışını difraksiyon sonuçlarından numunelerin triklinik bir kristal yapıya sahip olduğu belirlendi. Numunelerin AC iletkenliklerinin frekansla değişimi, elektriksel iletim mekanizmalarının bariyer sıçrama modeliyle tanımlanabileceğini gösterdi. Farklı frekanslar için elektriksel aktivasyon enerjisi değerleri AC iletkenliğin sıcaklıkla değişiminden belirlendi ve frekanstaki artışla azaldığı bulundu. Numunelerin dielektrik özellikleri frekans ve sıcaklığın bir fonksiyonu olarak araştırıldı. Dielektrik parametrelerin frekansla azaldığı ve sıcaklıkla belirli bir değere kadar arttığı ve sonra azaldığı gözlemlendi. Anahtar Kelimeler : Dielektrik özellik, AC iletkenlik, 1,10-Fenantrolin.

In this thesis, X-ray diffraction, AC electrical conductivity and dielectric properties of the complexes of 1,10-Phenanthroline have been investigated. It has been determined from X-ray diffraction results that the samples have a triclinic crystal structure. The variation of the AC conductivity with frequency of the samples has shown that their electrical conduction mechanism can be described by barrier hopping model. The values of electrical activation energy for different frequencies have been determined from the variation of AC conductivity with temperature and found to decrease with the increase in frequency. The dielectric properties of the samples have been investigated as a function of frequency and temperature. It has been observed that dielectric parameters decrease with frequency and increase with temperature to a certain value and then decrease. Keywords : Dielectric property, AC conductivity, 1,10-Phenanthroline. I
The investigation of dielectric properties of the complexes of phenanthroline
Keywords: Fizik ve Fizik Mühendisliği